Is this my hand? Body-ownership and the rubber hand illusion - Satoshi Shibuya; Satoshi Unenaka; Yukari Ohki (Japanese Society of Physical Fitness and Sports Medicine, 2015)
We perceive that our body belongs to us and is a coherent and unified entity. Therefore, body-ownership is fundamental to self-consciousness. To explore body-ownership in normal subjects, researchers have intensively used a bodily illusion known as the rubber hand illusion (RHI). This review article focuses on RHI studies. In a standard RHI paradigm, the sight of the participant's hand is occluded, while a life-sized fake hand is visible. Synchronous stroking of the fake and real hands with paintbrushes elicits a subjective sensation that the fake hand is their own. The RHI is generally demonstrated using a self-report questionnaire as a subjective measurement, and proprioceptive drift (i.e., mislocalization of the real hand toward the fake hand) as an objective measurement. There are two constraints for inducing the RHI: visuo-tactile synchrony and consistency between multisensory inputs and body representations. The RHI can also be induced by visuo-motor correlations: viewing movements of the rubber hand that are synchronous with movements of the real hand. In this RHI variant, participants experience body-ownership as well as agency, which is a type of bodily self-consciousness that one is initiating and controlling his/her own actions. Neuroimaging studies suggest that the RHI is associated with a wide range of neural substrates, including fronto-parietal networks. In sum, accumulating evidence from the RHI suggests that body-ownership is very flexible, and the brain can incorporate a non-corporal object into a person's own body.